Pengembangan E-modul Menggunakan Book Creator Dalam Mata Pelajaran Sejarah di SMA Negeri 1 Indralaya Utara - Oktara, Reska; Susanti, Retno (Educatio, 2026)
To support the quality of teaching and learning, educators need innovation in engaging teaching materials, especially in an era of rapidly advancing technology. This research aims to develop and test the effectiveness of e-module teaching materials using Book Creator in the subject of History, specifically regarding the entry and development of Hindu-Buddhist religion and culture in Indonesia. The method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research include 30 students from grade X of SMA Negeri 1 Indralaya Utara, with the e-module consisting of 103 pages showing an improvement in students' understanding. The developed teaching materials have been validated by three expert validators (in content, language, and media). Through the analysis obtained, 30 students achieved a classification of N-Gain 'High' with a score of 0.85, indicating that this e-module is effective in enhancing understanding of the material. The researcher.